USE OF SEQUENT ADSORPTION WITH ACTIVATED NATURAL ZEOLITE AND ACTIVATED CHARCOAL AS ADSORBENT TO IMPROVE THE QUALITY OF WASTE COOKING OIL - Ola, Pius D.; Taus, Elisabeth (Universitas Nusa Cendana, 2023)
Cooking oil which is exposed to high temperatures of up to 200 °C during the cooking process, leads to the formation of hazardous substances that are potentially dangerous to human health. However, people sometimes use the same cooking oil repeatedly without considering the negative effects that it causes. In this work, we investigated the use of two different types of adsorbent namely activated charcoal and activated zeolite sequentially to improve the quality of waste cooking oil (WCO) using the adsorption method. It was found that for 30 mL of WCO, the optimum dose of adsorbent was 7.5 g and the optimum contact time was 20 minutes. When these two types of adsorbent were applied sequentially for the purification of WCO at the optimum conditions, the result obtained indicated the lower value of the acid number, peroxide number, viscosity, and water content, compared to the WCO that treated only with a single type of adsorbent.